Red team : how to succeed by thinking like the enemy - Zenko, Micah (New York : Basic Books, a member of the Perseus Books Group, 2015)
"An international security expert shows how competitive organizations can get-and stay-ahead by thinking like their adversaries"--
"In Red Team, security expert Micah Zenko provides an in-depth investigation into the work of red teams, revealing the best practices, most common pitfalls, and most effective strategies of these modern-day Devil's Advocates. He shows how competitive organizations, from private corporations to whole governments, can and should mitigate risk by red teaming. A growing number of institutions are already using this approach, Zenko shows, but he argues that the potential of red teaming far exceeds its current applications. Drawing on hundreds of interviews and his own training at the U.S. Army's Red Team University (which he was the first civilian to attend), Zenko traces the history of red teaming, describes its current uses, and explores its vast potential in today's interconnected, multipolar world. The basic techniques of red teaming remain the same whether applied to the CIA, IBM, or the NFL, and executed correctly they can yield impressive results: red teams have given businesses an edge over their competition, confirmed vital CIA intelligence, and troubleshot dangerous military missions long before there were boots on the ground. But red teams are only as good as the leaders who commission them, and Zenko shows not only how to create an empowered red team, but also what to do with its advice. Essential reading for policy wonks and business leaders alike, Red Team will revolutionize the way organizations think about, exploit, compensate for, and correct their institutional strengths and weaknesses. Through illuminating case studies and never-before-told stories, Zenko shows how any group--from army units to credit card companies to sports teams--can win by thinking like the enemy"--
Best practices in red teaming -- Modern military red teaming -- Alternatives : intelligence community red teaming -- Adversaries : Homeland security red teaming -- Competitors : private-sector red teaming -- Modesty, misimpressions, and the future of red teaming.
Includes bibliographical references (pages 243-275) and index.
"A council on foreign relations book."
Keywords: Success in business; Risk management; Private security services; Competition